A hypothetical analysis on the impact of the Asean Free Trade Agreement in the local car industry / Norlaila Abdullah - Abdullah, Norlaila (Universiti Teknologi MARA Cawangan Pahang, 2000)
AFTA (ASEAN Free Trade Area) brings the ASEAN countries collectively into the frontier of today's world market. This is an economic issue that every Heads of States and Government of each member country has to resolve. A member country resolution is focused towards a move that is in the best interest of the member country and the ASEAN members as a whole. ASEAN countries having relatively bigger growth in poputation and natural resources; but its economic reputation is still incomparable to India, South Korea, and China, the emerging neighboring countries. These countries will continuously develop its product standards and markets alongside with direct inflow of foreign investments. Consequently, if ASEAN countries will not adopt changes on its economic strategy then it will be left behind. ASEAN needs to build good economic reputation to the international market by producing quality products and designs that are relatively comparable with those products in the developed countries. This requires member countries to be economically integrated to take advantage of every resources available such as techonology, information technology infrastructure, human and capital resources. AFTA is the avenue for ASEAN member countries to achieve these goals; thus strengthening its competitive advantage in terms of product quality, pricing, access to informations and human resources capabilities. Should this move fails, some member countries will be economically lesser at par while others with good financial and economic strenght would find it less fit to survive as its market and other resources are relatively smaller to compete with the giants in the international arena.